Analisis Kinerja Bank Syariah di Indonesia Dengan Pendekatan Sharia Maqashid Index (SMI)Tahun 2016-2018 - Sari, Ihda Lasna; Isnandar, Fajri Ryan (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
This study aims to analyze the performance of Islamic banks using the Sharia Maqashid Index.The variables used in this method adopt Abu Zahraâ€™s maqashid sharia theory, namely Tahdhib alFardh (Individual Education), Iqamah al Adl (Enforcing Justice), and Jalb al Maslahah (Achievementof welfare). From these variables finally obtained 10 performance ratios used in measuring theperformance of Islamic banks, which are then given the respective weights. The existence of thismethod originated from the inadequacy of Islamic bank performance measurements that use generalperformance measurements commonly used in conventional banks in general. This performancemeasurement was promoted by Mustafa Omar, et al in 2008 in his research entitled â€œThe PerformanceMeasures of Islamic Banking Based on the Maqasid Frameworkâ€. The object of this research is 12BUS in Indonesia. The data used is the annual report of 12 BUS in 2016-2108. The results of thisstudy indicate that among 12 BUS in Indonesia, Bank Panin Dubai Syariah obtained the highestSMI value with an index value of 36.75. These results indicate that Panin Dubai Syariah Bankhas a good performance using the Sharia Maqashid Index. Rank 12 BUS in Indonesia as follows:Bank Panin Dubai Syariah, Bank Victoria Syariah, BCA Syariah, Bank Muamalat Indonesia, BankSyariahBukopin, BTPN Syariah, Bank BRI Syariah, Bank BNI Syariah, Bank SyariahMandiri,MaybankSyariah Indonesia, Bank JabarBanten Sharia, and Bank Mega Syariah.